The Collective Imagination and the Limitations for the Tianxia to Replace the Westphalian World Order - Giedrius Česnakas (Politologija, 2022)
The collective political imagination establishes world orders that define how political communities interact. The relative power of the West allowed the introduction of the first global world order, known as the Westphalian. However, the increasing relative power of the People’s Republic of China allows it to promote an alternative world order vision, which is the result of its political imagination. Zhao Tingyang’s re-imagined hierarchic Tianxia order is seen as a challenger to the Westphalian order. This paper analyzes whether the Tianxia order can replace the Westphalian, considering the contemporary global political environment. The discussion is based on Jeffrey Legro’s theory of collective ideas and foreign policy change, applying it to world order replacement analysis. The findings suggest that the Tianxia has significant limitations in replacing the Westphalian world order. The Westphalian order orthodoxy remains strong. The order is also adaptable, capable of including hierarchical elements. Despite the increase of the PRC’s relative power and its greater capabilities to shape norms with domestic support, continuity usually prevails, so the habit of sovereignty prevails over hierarchical order. Finally, the article argues that the Tianxia order is not resilient to the anarchic-competitive element of human nature.